(untitled) (Proceedings of the International Conference on Education, 2019)
Musical education belongs to significant spheres of personality development and human expression. Music develops human imagination, enhances the emotional experience, evokes the human ability to perceive the organised world of sounds and stimulates the esthetical experience of this world. Many studies have shown that the importance of musical education is more important for primary school pupils than in later years. If before this age, in the families or schools the music education is not given enough attention, the child loses a lot (musical receptiveness, specific visual thinking), and later this kind of abilities for various reasons (disharmony of physical, emotional development, etc.) are more suppressed. Therefore, much of significance must be devoted to the musical education of future primary school teachers. The research data from qualitative and quantitative study analysis have highlighted the peculiarities of musical and pedagogical psychological competencies of primary school teachers.